2018
DOI: 10.15171/mejdd.2018.125
|View full text |Cite
|
Sign up to set email alerts
|

The Right Liver Lobe Size/Albumin Concentration Ratio in Identifying Esophageal Varices among Patients with Liver Cirrhosis

Abstract: BACKGROUND It is necessity to work more on non-invasive markers like right liver lobe size/albumin concentration ratio for predicting esophageal varices. We aimed to see the right liver lobe/albumin ratio in identifying esophageal varices among patients with cirrhosis caused by hepatitis B and C. METHODS A cross-sectional study was conducted among all indoor patients admitted to the Department of Internal Medicine, Pakistan Atomic Energy Commission, General Hospital, Sector H-11/4 Islamabad, Pakistan, durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 24 publications
3
5
0
Order By: Relevance
“…Prediction of EV considering noninvasive approaches has obtained considerable attention, and numerous investigations have been carried out to invent noninvasive parameters to facilitate the anticipation of EV in CLD patients with an objective of declining cost and burden on endoscopy 20 . In our study, there were 123 (82%) patients with EV who were included, which was consistent with previously reported studies from different countries like Pakistan, India, Serbia, and Egypt 14,18,21,22 . In accordance with the previous study, 14,22 the grading of Child‐Turcotte‐Pugh, we noticed that patients with grade A were 72 (48%), which was followed by grade B (54, 36%), and grade C (24, 16%).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Prediction of EV considering noninvasive approaches has obtained considerable attention, and numerous investigations have been carried out to invent noninvasive parameters to facilitate the anticipation of EV in CLD patients with an objective of declining cost and burden on endoscopy 20 . In our study, there were 123 (82%) patients with EV who were included, which was consistent with previously reported studies from different countries like Pakistan, India, Serbia, and Egypt 14,18,21,22 . In accordance with the previous study, 14,22 the grading of Child‐Turcotte‐Pugh, we noticed that patients with grade A were 72 (48%), which was followed by grade B (54, 36%), and grade C (24, 16%).…”
Section: Discussionsupporting
confidence: 90%
“… 20 In our study, there were 123 (82%) patients with EV who were included, which was consistent with previously reported studies from different countries like Pakistan, India, Serbia, and Egypt. 14 , 18 , 21 , 22 In accordance with the previous study, 14 , 22 the grading of Child‐Turcotte‐Pugh, we noticed that patients with grade A were 72 (48%), which was followed by grade B (54, 36%), and grade C (24, 16%). Alempijevic et al 15 identified 22.3%, 33%, 16%, and 4.3% of the patients with grade I, II, III, and IV esophageal varices, respectively, and 24.5% of the patients with no esophageal varices with an upper GI endoscopy examination.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations